2020
DOI: 10.1016/j.virol.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the evolutionary features of viral overlapping genes by discriminant analysis

Abstract: Please cite this article as: Pavesi, A., New insights into the evolutionary features of viral overlapping genes by discriminant analysis, Virology, https://doi. AbstractOverlapping genes originate by a mechanism of overprinting, in which nucleotide substitutions in a pre-existing frame induce the expression of a de novo protein from an alternative frame. In this study, I assembled a dataset of 319 viral overlapping genes, which included 82 overlaps whose expression is experimentally known and the respective 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 81 publications
1
78
0
1
Order By: Relevance
“…ORF3d comprises 58 codons (including STOP) near the beginning of ORF3a ( Table 1 ), making it longer than the known genes ORF7b (44 codons) and ORF10 (39 codons) ( Supplementary file 1 ). ORF3d was discovered independently by Chan et al, 2020 as ‘ ORF3b ’ and Pavesi, 2020 as ‘hypothetical protein’. Due to this naming ambiguity and its location within ORF3a , ORF3d has subsequently been conflated with the previously documented ORF3b in multiple studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…ORF3d comprises 58 codons (including STOP) near the beginning of ORF3a ( Table 1 ), making it longer than the known genes ORF7b (44 codons) and ORF10 (39 codons) ( Supplementary file 1 ). ORF3d was discovered independently by Chan et al, 2020 as ‘ ORF3b ’ and Pavesi, 2020 as ‘hypothetical protein’. Due to this naming ambiguity and its location within ORF3a , ORF3d has subsequently been conflated with the previously documented ORF3b in multiple studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous research reports, angiotensin converting enzyme 2 (ACE2), which is highly expressed in lung and heart, is a functional receptors for severe acute respiratory syndrome coronavirus (SARS-CoV), and is likely to play a critical role in infection of the myocardium [13] , [14] . SARS-CoV-2 may have the same mechanism of infection as SARS-COV because the viruses are highly homologous in genome [15] , [16] , [17] . At the same time, recent studies have demonstrated that ACE2 has a high binding affinity with spike protein of SARS-CoV-2 [18] , [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed four ORFs overlapping 3a 6,[8][9][10][11][12][13] : 3c (41 codons), 3d (57 codons), 3b (22 codons, a truncated ortholog of SARS-CoV ORF3b), and a subset of 3d (33 codons). ORF3c was proposed using synonymous constraint across 6 closely-related strains 8 and a broader set of Sarbecoviruses 9 , although on its own such evidence could also stem from other overlapping functional elements (and is abundant in SARS-CoV-2 even outside dual-coding regions), and using ribosome…”
Section: Orf3c Is a Novel Functional Proteinmentioning
confidence: 99%
“…The paper introducing SARS-CoV-2 also shows 3b (which overlaps 3a in SARS-CoV but is truncated in SARS-CoV-2, with several in-frame stop codons) 1 . Other publications [5][6][7][8][9][10][11][12][13] include different subsets, use different names, or propose additional ORFs (including 3c and 3d overlapping 3a). NCBI annotates SARS-CoV (NC_004718.3) orthologs of 3a, 6, 7a, 7b, and 9b, but 8 is split into 8a and 8b, 3b is included, and neither 9c nor 10 are included.…”
Section: Introductionmentioning
confidence: 99%